2013
DOI: 10.1002/ptr.5036
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin I Mediates Neuroprotective Effect Through Attenuation of Quinoprotein Formation, p‐p38 MAPK Expression, and Caspase‐3 Activation in 6‐Hydroxydopamine Treated SH‐SY5Y Cells

Abstract: 6-Hydroxydopamine (6-OHDA) selectively enters dopaminergic neurons and undergoes auto-oxidation resulting in the generation of reactive oxygen species and dopamine quinones, subsequently leading to apoptosis. This mechanism mimics the pathogenesis of Parkinson's disease and has been used to induce experimental Parkinsonism in both in vitro and in vivo systems. In this study, we investigated the effects of curcumin I (diferuloylmethane) purified from Curcuma longa on quinoprotein production, phosphorylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…With the higher concentrations of H 2 O 2 (500 and 1,000 µM), 20 µM of curcumin showed the best neuroprotection; whereas with the lower concentrations of H 2 O 2 (100 and 300 µM), 5 µM of curcumin was sufficient to improve cell viability. Protecting SH-SY5Y cells from oxidative stress and beta amyloid induced neurotoxicity by treating them with curcumin have also been shown in other studies [6,7,17,[27][28][29]. Further research is needed to explain the mechanism behind the differences in cell viability when curcumin is used as pretreatment versus post-treatment in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 87%
“…With the higher concentrations of H 2 O 2 (500 and 1,000 µM), 20 µM of curcumin showed the best neuroprotection; whereas with the lower concentrations of H 2 O 2 (100 and 300 µM), 5 µM of curcumin was sufficient to improve cell viability. Protecting SH-SY5Y cells from oxidative stress and beta amyloid induced neurotoxicity by treating them with curcumin have also been shown in other studies [6,7,17,[27][28][29]. Further research is needed to explain the mechanism behind the differences in cell viability when curcumin is used as pretreatment versus post-treatment in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, nephrocizin is capable of diffusing through the cell membranes and scavenges the hydroxyl radical directly. Similarly, Meesarapee et al [125] showed that pretreatment of human neuroblastoma SH-SY5Y cells exposed to 6-OHDA by curcumin effectively reduces cell death by decreasing the levels of quinone-bound proteins.…”
Section: Oxidative Stressmentioning
confidence: 93%
“…Polyphenols also modulate the mitogen-activated protein kinase (MAPK) pathways that is involved in cell survival and apoptosis, and might have roles in the protection against oxidative stress. For example, curcumin [125] and naringenin [112] reduced the phosphorylation of MAPKs and the levels of cleaved caspase-3 in human neuroblastoma SH-SY5Y cells exposed to 6-OHDA. Curcumin and naringenin also prevented intracellular Ca 2+ increases, ROS production, and decreased apoptosis through mitigation of the expression and activity of pro-apoptotic factors [126].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In addition, flavonoids from Selaginella species have the ability to increase the expression and activity of anti-oxidative enzymes endogenously [104], and the aqueous extract of Selaginella suppresses rotenone induced neurotoxicity, attenuated locomotor dysfunction, oxidative stress, and mitochondrial dysfunction in Drosophila melanogaster [105]. Polyphenols may also target MAPK pathways and apoptosis, since phosphorylation of MAPK and expression of cleaved caspase 3 were reduced in 6-OHDA induced SHSY-5Y cells by curcumin [106]. Similarly, the phosphorylation of NF-kB, JNK, and ERK was inhibited by flavone baicalein in MPP + -induced primary astrocytes and indicated its implication in the treatment of PD [107].…”
Section: Neuroprotective and Anti-inflammatory Role Of Polyphenolsmentioning
confidence: 99%